Are Periodic Oscillations of Sea Surface Height Inherent to River Plumes? - Zavialov, Peter O. (Frontiers in Marine Science, 2021)
We analyze high temporal resolution (10 min) sea surface height (SSH) data records from pressure sensors deployed on the inner shelf within the plumes of the Mzymta and the Vulan, two small-to-medium size rivers in the Russian sector of the Black Sea coast. The SSH was recorded in parallel with meteorological parameters, averaged over the same 10 min intervals. While the low-frequency changes of the SSH at periods of 6 h or longer accounted for about 90% of the total variability and were strongly correlated with the wind, superimposed on them there always existed higher frequency oscillations whose characteristic periods ranged from 70 to 230 min, and the amplitudes spanned between 1 and 19 cm, not correlated with either the wind stress or atmospheric pressure. Furthermore, the amplitudes and the periods of these high-frequency oscillations appeared to be proportional to the horizontal scale of the river plume, as well as to each other. A very simple semi-analytical model focused on the interplay between the plume’s mass and the momentum budgets demonstrated that periodic oscillations of the sea surface height should be inherent to river plumes, and also helped to explain the abovementioned dependencies.